The hidden Ismailia imams and their role in establishing the Fatimid state (Journal of Imam Al-Kadhim College, 2024)
In these papers, we seek to research the Ismaili imams and their role in crystallizing the Ismaili movement, as well as the role of the Syrian city of Salamiya, which was chosen by the four hidden Ismaili imams to embrace the call, and how to prepare preachers there and arrange them as preachers and borders, and then send them to cities and islands to spread the ideas and beliefs of Ismailism, and how this call maintained its activity. Religiously and politically, and ways to continue it according to a complex, secret philosophical approach stemming from their Ismaili faith, and from there they paved the way for the establishment of a Shiite state sponsored by the Ismaili movement, and recognized it as a Shiite sect among the Muslim sects. The first of these signs was the sending of Imam Hussein bin Ahmed bin Abdullah bin Muhammad bin Ismail, the two preachers, Ibn Hawshab. To Yemen, Abdullah the Shiite to Morocco, and from there the Sicilian essence to conquer Egypt, not to establish the foundations of the state.